Impact of Power Plant on Environment: A Legal Challenge: Exploring the Consequences of Power Plants on the Environment and Legal Implications (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The advent of industrialization in the second half of 18th century was a watershed moment inthe history of humankind. It was the moment when the humankind denuded itself from the shackles ofthe past and strived to pave a way for a beautiful future. A future, when realized, was both blessed withthe charm of technological advancements but at the same time was plagued by gruesome inequality anda terrible environment to live in. Since the end of the second world war, the modern nation-states haveparticipated in numerous conventions to address this deteriorating problem of environmentaldegradation. The problem of environmental degradation has been attributed to the technologicaladvancements which humankind has achieved with the help of industrialization which was consequentlydone with utter disregard to the environment by not focusing on the sustainable mode of development.Most of the environmental degradation was a direct result of energy generation through burning of fossilfuels. Life without energy sector is unthinkable in 21st century. Energy sector is considered as one of thechief contributors in the environmental degradation. It impacts environment at multiple stages of itsdevelopment and use including in construction, electricity generation, dissemination anddecommissioning and disposal. The recently held 26the Climate Change Conference of the UnitedNations (COP26) reiterated the urgent need and called upon the participating nations to reduce thegreenhouse gas emissions and attain the net zero carbon emissions with alacrity. Against this backdrop,this article is an attempt to examine the significant impact of power plants on the environment and legalissues which are incidental to it with a special reference to India.